Screening of short-day onions for resistance to Stemphylium leaf blight in the seed-to-bulb stage (stage I) and bulb-to-seed stage (stage II) - Chandel, Rahul; Kamil, Deeba; Singh, Shrawan; Kumar, Amrender; Patel, Rumit; Verma, Priyanka; Zimik, Masochon; Khar, Anil (Frontiers in Plant Science, 2022)
Stemphylium leaf blight, caused by Stemphylium vesicarium, is a very important fungal disease in onions since its epidemics are able to affect both the bulb yield and seed quality. The aim of this study was to screen onion genotypes at Stage I (seed to bulb) and further screen the identified resistant and susceptible genotypes at Stage II (bulb to seed). One hundred and fifty-seven genotypes were screened against SLB under artificially inoculated field conditions. Results revealed a significant variation among the morphological and biochemical traits studied. Correlation studies revealed a significant and negative correlation between percent disease incidence (PDI), pseudostem width, neck thickness, and dry matter. Fifteen genotypes were identified as moderately resistant, and the rest were categorized as susceptible. Bulbs of the genotypes, identified as moderately resistant, were again screened for resistance in Stage II. All the genotypes were categorized as moderately susceptible. Biochemical analysis revealed that total foliar phenol content, pyruvic acid, catalase, and peroxidase increased up to 20 days after inoculation (DAI) and thereafter declined. Protein content was highest in the initial stage and declined at 10, 20 and 30 DAI. The higher biochemical activity was observed in MR category genotypes compared to the susceptible ones. Correlation analysis showed a highly significant and negative correlation of PDI with total foliar phenol content (TFPC), pyruvic acid, catalase, peroxidase and protein content. To conclude, it was observed that screening against SLB should be done at both stages to identify a resistant onion genotype. Indirection selection for genotypes with high dry matter, higher phenols and enzymes may be an alternative pathway to select genotypes for a robust resistance breeding programme.